Gene Expression Profile in Experimental Mesangial Proliferative Glomerulonephritis - Yasukatsu Izumi; Yasuhiro Izumiya; Masayuki Shiota; Tokihito Yukimura; Satoshi Shiojima; Masateru Yamada; Tadashi Kadowaki; Susumu Katsuma; Akira Hirasawa; Gozoh Tsujimoto; Hiroshi Iwao (Elsevier, 2004)
We analyzed gene expression in rat anti-Thy1 antibody-induced glomerulonephritis by using the cDNA microarray method. Ninety-seven genes that differed by more than 1.5-fold intensity in comparison with the controls were selected. Cluster analysis showed that the expression of genes associated with inflammation reached maximum levels at 24 h, while genes involved in the development of fibrosis increased at 7 days after injection. Microarray analysis of animal disease models may be a powerful approach for understanding the gene expression programs that underlie these disorders. Keywords:: cDNA microarray, nephritis, gene expression